Dibujos didácticos y memoria de la Antigüedad romana: Las glosas de los Proverbios del Marqués de Santillana ilustradas en la Suma de virtuoso deseo - Beltrán, Rafael (Troianalexandrina, 2014)
Abstract The Marquis of Santillana’s Proverbios is one of his most important poetic works and his most well-known text from the fifteenth to the sixteenth centuries. The central part of the poem presents a group of biblical and Roman examples, some of them glossed by Santillana himself. The Suma de virtuoso deseo (BNE, ms. 1518), a miscellaneous historical text, provides variants in some of these glosses in prose, together with illustrations. The interpretation of these images, which seek a didactic and mnemonic effect, and the interpretation of the symbolic set represented by both texts and images, help us understand some issues related to the metamorphosis of the vision of Antiquity and the written transmission of history in this particular period of the Spanish Middle Ages.